Effectiveness of Service Innovation, Where Service Failure is an Imperative Issue for a Small Food-Service Brand: Case Study Approach - Huq Bin Shahriar, Shamsul; Ul Islam and Md. Fayjullah Khan, Mahbub (British Journal of Marketing Studies, 2018)
This article confers regarding effectiveness of service innovation in a small restaurant environment; where, the subject of repeated incidences of service failure is a common issue. Moreover, inadequately designed recovery actions putted the final nail in the coffin. For in-depth understanding of the exacting instance surround by real-life situation a single case study approach was adopted. A restaurant namely ‘Chittagong Express’ was considered for the in- depth study. This conscientious study is qualitative in nature; required data were collected in through of in-depth interviews, from the duo sides; management in the one side and customers on the other. The major findings from study confirmed that the food service brand is facing additional challenges to shield its brand image. Furthermore, post failure negative consequences, i.e. less repurchasing intention of the customers, less trust and customer loyalty towards the brand, negative post recovery emotions and discomfort were found in this case. Primarily, the efforts vis-à-vis the service innovation was incredibly appreciated by the customers, nonetheless, myopic visualization with reference to the appropriate customer satisfaction can be marked as the main reason of the predicament.